PENGEMBANGAN KREATIVITAS GURU DALAM MENINGKATKAN KUALITAS PENDIDIKAN - Mulyati, Yati Siti (Jurnal Inovasi Pendidikan, 2011)
Creativity has two components: the importance of creativity in their daily activities and beliefs of the importance of creativity in schools. It is clear that without the creativity of human beings can not enjoy the pleasure and meaning of life, and without creativity we do not have art, literature, science, innovation, problem solving, and progress. Developing creativity in class is the main and important factor. Creativity can be trained and taught to students. Teachers who train and teach creativity to students, teachers must also was a creator. Teachers who understand creativity can choose content, lesson plans, organize material, and appropriate tasks in a way to help students develop skills and attitudes necessary for creativity. To do this well, teachers need a strong foundation in research and theories about creativity and variety of teaching and management strategies for linking research and practice.  Parallel to the learning process of creativity. Students who use the content in creative ways, learning content properly. Students also learn strategies to identify problems, make decisions, and determine solutions in schools, and outside of school. Classes are organized to develop creativity into learning and wonderful place, that is, ?glad to know?. Next, discuss what, how, why creativity be taught and the link between creativity with motivation, and classroom organization, and the factors that affect creativity.